2011
DOI: 10.3174/ajnr.a2463
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Findings in Patients with Secondary Intracranial Hypertension

Abstract: BACKGROUND AND PURPOSE: IH can alter the configuration of anatomic structures of the central nervous system. We determined the sensitivity and specificity of MR imaging to detect these changes in patients with secondary IH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
4
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 31 publications
4
44
4
4
Order By: Relevance
“…Due to the invasive nature of testing CSFP, noninvasive measures are desirable. Other techniques that have been explored include IOP measurement, 19 optic nerve sheath width measurement by ultrasonography 20 or MRI, 21,22 and an approach using transcranial Doppler technology. 23 Unfortunately, limitations exist for each of these techniques as well as the technical approach that is being used to estimate CSFP.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the invasive nature of testing CSFP, noninvasive measures are desirable. Other techniques that have been explored include IOP measurement, 19 optic nerve sheath width measurement by ultrasonography 20 or MRI, 21,22 and an approach using transcranial Doppler technology. 23 Unfortunately, limitations exist for each of these techniques as well as the technical approach that is being used to estimate CSFP.…”
Section: Discussionmentioning
confidence: 99%
“…The variability associated with subjective rating may partly explain reported differences in frequency of these findings in IIH and secondary IH. 3,4 Automated quantitation of the globe distortion may help to overcome the limitations associated with the subjective assessment and thereby improve diagnostic accuracy. The significant association between the subjective rating and the computer-derived GF measure supports the feasibility for a reliable automated quantitation of globe flatness.…”
Section: Discussionmentioning
confidence: 99%
“…Work by Agid et al 3 assessing several cross-sectional neuroimaging signs seen in IIH suggests that posterior globe flattening has the strongest diagnostic value, with specificity of 100%, whereas optic nerve protrusion was not significantly associated with IIH. In contrast, Rohr et al 4 assessed similar signs in patients with secondary IH and reported specificity of 78% for globe flattening and 100% for optic disc protrusion. Both studies, however, used subjective visual inspection to determine the presence of flattening and optic nerve protrusion.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A widespread involvement of the venous sinuses was associated with very high CSF pressure. They hypothesized that IH compresses the dural sleeve of the venous sinuses 38 . Regardless of cause or effect, patients with IIH are likely to have raised venous pressures and stenotic lesions in their lateral venous sinuses.…”
Section: Cross Sectional Mri/ Ct Findings In Iihmentioning
confidence: 99%